2023
DOI: 10.1039/d2cc06531b
|View full text |Cite
|
Sign up to set email alerts
|

C2-insertion into a fullerene orifice

Abstract: The C2-insertion into a fullerene orifice enables an expansion of the inner space while the C2 unit originated from N-phenylmaleimide is merged with the fullerene skeleton possessing an orifice enlarged from an octagon to a decagon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…We also found that a consecutive addition of aromatic 1,2‐diamine gives a huge orifice which allows for H 2 O, N 2 , Ar, and MeOH to be encapsulated [13] . This method could also be used for the synthesis of bilaterally π‐extended C 60 derivatives, [14] as well as for the creation of π‐extended C 70 derivatives [15] . Importantly, the nucleophilicity of diamines was found to change annulation and orifice cutting modes (Figure 1), such as A (fused pyrazine, 20‐atom ring) and B (fused imidazole, 17‐atom ring) [16] .…”
Section: Introductionmentioning
confidence: 76%
“…We also found that a consecutive addition of aromatic 1,2‐diamine gives a huge orifice which allows for H 2 O, N 2 , Ar, and MeOH to be encapsulated [13] . This method could also be used for the synthesis of bilaterally π‐extended C 60 derivatives, [14] as well as for the creation of π‐extended C 70 derivatives [15] . Importantly, the nucleophilicity of diamines was found to change annulation and orifice cutting modes (Figure 1), such as A (fused pyrazine, 20‐atom ring) and B (fused imidazole, 17‐atom ring) [16] .…”
Section: Introductionmentioning
confidence: 76%
“…[4] A huge orifice is also useful for trapping a chemically labile species such as H 2 O 2 under mild conditions (C) as shown by Lu, Gan, and co-workers in 2018. [12] The raise in awareness to gain huge orifices led to the successive reports on 21-membered-ring orifices recently (D [13] and E [14] ). The latter one was prepared from F, [15] which is structurally related to A while F has a reactive carbonyl group on the 20-membered-ring orifice.…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of [5,6]-open PCBM has been hampered due to a rapid chemical transformation into a [6,6]closed analogue, [24][25][26][27] bis- [5,6]-open OC is thermally stable even at 260 1C without showing any isomerism owing to the disfavoured generation of an intermediate having two [5,6]-closed structures at the cis-1 disposition in close proximity. 28,29 Furthermore, bisfunctionalization of C 60 (bis- [6,6]PCBM and ICBA) usually leads to a greater V OC , owing to the higher-lying LUMO level. 30 Therefore, the bis- [5,6]-open structure in the OC is highly attractive for application in PSCs as the ETM.…”
mentioning
confidence: 99%